English English - Auliya, Dewi Nur; Al Umami, Habiba (Elite : English and Literature Journal, 2024)
This research aims to examine how Indonesian netizens of X consider physical bullying in wider scope, which is social media (cyber-world) through X. Researchers analyze traditional bullying that occurs in Indonesia but is used as discourse on social media (cyber). Therefore a netizen attitude assessment system appears in comments and posts, especially those related to affect, assessment, and appreciation. The method used in this research is Qualitative research under Discourse Analysis methods, with the social media data source "X" with the keywords #bullying and #bullyingcilacap, while the data analyzed is in the form of words or lexis related to the appraisal system. The findings of this research are in the form of a negative judgment attitude followed by an attitude of affect and appreciation in posts about bullying cases that occurred in Indonesia. This shows that the writer or netizen is very angry and worried about the immoral act of bullying. However, a form of positive judgment attitude was also found where netizens sympathized and cared about justice for victims of bullying.